2004
DOI: 10.1086/426963
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Infrared and X-Ray Flux Changes Following the 2002 June Outburst of the Anomalous X-Ray Pulsar 1E 2259+586

Abstract: We present the results of a near-infrared monitoring program of the anomalous X-ray pulsar 1E 2259ϩ586, performed at the Gemini Observatory. This program began 3 days after the pulsar's 2002 June outburst and spans ∼1.5 yr. We find that after an initial increase associated with the outburst, the near-infrared flux decreased continually and reached the preburst quiescent level after about 1 yr. We compare both the near-infrared flux enhancement and its decay to those of the X-ray afterglow and find them to be r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
64
2

Year Published

2005
2005
2008
2008

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 28 publications
11
64
2
Order By: Relevance
“…For example, a correlation in the decays of the X-ray and near-IR fluxes in 1E 2259+586 was observed following the 2002 outburst (Tam et al 2004); a similar correlation was reported for XTE J1810−197 . However, in other instances, the two fluxes were not correlated, as for 1E 1048−5937 , and Durant, van Kerkwijk, & Hulleman 2004.…”
Section: Other Wavelengthssupporting
confidence: 65%
“…For example, a correlation in the decays of the X-ray and near-IR fluxes in 1E 2259+586 was observed following the 2002 outburst (Tam et al 2004); a similar correlation was reported for XTE J1810−197 . However, in other instances, the two fluxes were not correlated, as for 1E 1048−5937 , and Durant, van Kerkwijk, & Hulleman 2004.…”
Section: Other Wavelengthssupporting
confidence: 65%
“…Moreover, it has become evident that X-ray flux enhancement of the persistent emission of SGRs is correlated with their burst rate, making it difficult to compare the fluxes among different SGRs without knowing their burst history (see Woods & Thompson 2004). Tam et al (2004) argued that IR thermal surface emission (within the magnetar model) is ruled out during the correlated X-ray/IR flux decay phases of 1E 2259+586 (implausibly high implied brightness temperature), suggesting the magnetospheric origin for the IR enhancement. Alternatively, the IR flux can be due to reradiation by material in the vicinity of the the pulsar.…”
Section: Discussionmentioning
confidence: 99%
“…The IR and X-ray fluxes subsequently decayed in a similar way, suggesting a close link between the emission processes in these two energy ranges. This was interpreted as evidence for a non-thermal, magnetospheric origin of the IR radiation [230], but Ertan et al [62] showed that the data can also be explained as emission from a residual disk pushed away by an energetic flare and gradually relaxing back to its original configuration.…”
Section: Optical and Infraredmentioning
confidence: 99%